2015
DOI: 10.1080/20549547.2015.11435410
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Historiography in Early China

Abstract: This paper examines the moral ambiguity that surrounded alcohol consumption in early China and the ways in which the use and abuse of alcohol served as a measure to judge the past. Rule-guided drinking was part of social life, but, importantly, it was also a corner stone in sacrificial ritual and therefore an important measure to please the spirit world. In assessing the past, early Chinese writers often judged rulers and their regimes based on the way they handled alcohol and ritualized drinking. Moderation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Though doctors fretted about the damage that alcohol, with its heating effect, could do to the body, it remained central to ritual and social life. Roel Sterckx has suggested that the sign of virtue when it came to alcohol was using it responsibly in a ritual context, not avoiding it altogether; this happy medium may have satisfied healers also (Sterckx, 2015). Tea, too, drew critical scrutiny from doctors, regardless of its moral benefits.…”
Section: Food and Health In Pre‐modern Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Though doctors fretted about the damage that alcohol, with its heating effect, could do to the body, it remained central to ritual and social life. Roel Sterckx has suggested that the sign of virtue when it came to alcohol was using it responsibly in a ritual context, not avoiding it altogether; this happy medium may have satisfied healers also (Sterckx, 2015). Tea, too, drew critical scrutiny from doctors, regardless of its moral benefits.…”
Section: Food and Health In Pre‐modern Chinamentioning
confidence: 99%
“…For their part, Buddhists advocated abstaining from both meat and alcohol, key ingredients in ancient China's sacrificial and social culture (Kieschnick, 2005; Laudan, 2013; Sterckx, 2015). They objected to meat consumption not only, or even primarily, because it violated the prohibition against killing, but also because meat was thought to stimulate and arouse the eater, thereby making it harder to achieve the detachment required to attain enlightenment.…”
Section: Food and Health In Pre‐modern Chinamentioning
confidence: 99%
“…11 The Chinese Government's austerity drive from 2013, which discouraged consumption of expensive wines and other luxuries, had much less influence on lower-quality wines, which in China are by far the most voluminous. Fluctuating tolerance for excessive alcohol consumption is an abiding theme in China's long history (Sterckx, 2015).…”
Section: Asia's Wine Production and Import Growthmentioning
confidence: 99%